Self-efficacy as a mediator of the relationship between subjective well-being and general health of military cadets - Luciane Albuquerque Sá de Souza; Ana Raquel Rosas Torres; Genário Alves Barbosa; Tiago Jessé Souza de Lima; Luana Elayne Cunha de Souza (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The objective of this study is to investigate the role of self-efficacy beliefs as a mediator of the relationship between the subjective well-being and general health of military cadets (police and firefighters). For this study, 228 cadets participated, the majority being Military Police officer candidates (65%), male (79%), between 17 and 34 years of age (99%), and unmarried (74%). They responded to questionnaires on general health (GHQ-12), perceived general self-efficacy, to the multiple scales that cover subjective well-being, and demographic questions. Initial regression analyses indicate the predictive power of subject well-being regarding general health. Subsequently, the mediation analyses provide satisfactory evidence for the role of perceived self-efficacy as a mediator of the relationship between the subjective well-being variables and the overall health of military cadets. The implications of these results for the professional training of the cadets are discussed.